Analysis of energy losses reduction potential on the distribution line of campus building through electric power quality improvement - Andi Pawawoi; Zuheldi Zuheldi; Fajril Akbar; Refdinal Nazir (Institute of Advanced Engineering and Science, 2020)
In public and commercial buildings, the reduction of electricity consumption activities can be conducted through 3 paths, including improving the quality level of electric power, increasing the efficiency of electrical equipment, and reducing the waste of electric energy use. In this paper, the energy losses reduction potential on the distribution line of Engineering Faculty, Andalas University buildings through electric power quality improvement are analyzed. Power Quality (PQ) variables that considered in this analysis include power factor, unbalance current load and harmonics distortion. Analysis of correlation between PQ variables is required to determine the power loss on the distribution line of buildings. Using data of PQ variables recorded by Fluke Power Analyzer 435 series II, the energy losses of the distribution line without/with PQ improvement for each building is calculated. Analysis results have shown that the reduction potential is proportional to the value of PQ variables. Administrative faculty building with poor power quality has the potential to reduce its energy losses on the distribution line by 52.62% through power quality improvement. Civil engineering building group with quite good power quality only has the potential to reduce energy losses by 32.81%. Overall, the buildings in this faculty have the potential to reduce energy losses on distribution lines by 34.42% through its power quality improvement.